2021
DOI: 10.1101/2021.01.22.21250336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single nuclei profiling identifies cell specific markers of skeletal muscle aging, sarcopenia and senescence

Abstract: Aging is accompanied by a loss of muscle mass and function, termed sarcopenia, which causes numerous morbidities and economic burdens in human populations. Mechanisms implicated in age-related sarcopenia include inflammation, muscle stem cell depletion, mitochondrial dysfunction and loss of motor neurons, but whether there are key drivers of sarcopenia is not yet known. To gain deeper insights into age-related sarcopenia, we performed transcriptome profiling on lower limb muscle biopsies from 72 young, old and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Basal expression of key senescence marker, p21, is low in skeletal muscle of adult mice relative to other tissues, with little‐to‐no change by 27+ months of age (Yousefzadeh et al, 2020 ). However, when assessed via single nuclear RNA‐seq, there is a small population of myonuclei from older individuals that express a relatively high amount of p21 (Perez et al, 2021 ). Further, previous work from our lab shows that human primary myotubes can express high levels of inflammatory cytokines in response to environmental stimuli (Varma et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Basal expression of key senescence marker, p21, is low in skeletal muscle of adult mice relative to other tissues, with little‐to‐no change by 27+ months of age (Yousefzadeh et al, 2020 ). However, when assessed via single nuclear RNA‐seq, there is a small population of myonuclei from older individuals that express a relatively high amount of p21 (Perez et al, 2021 ). Further, previous work from our lab shows that human primary myotubes can express high levels of inflammatory cytokines in response to environmental stimuli (Varma et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐nine studies measured the aforementioned skeletal muscle characteristics in young and old adults. 42 , 60 , 63 , 65 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 The details of the included studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…By hybridizing a fluorescent probe to the target RNA, ISH-based approaches (e.g., MERFISH, seqFISH+) quantify gene expression levels using fluorescent signals (Eng et al, 2019;Moffitt et al, 2018). ST analysis has been used to study aging and aging-related diseases in tissues including the brain, muscle, synovium, and joints Hardt et al, 2021;Perez et al, 2021;Vickovic et al, 2022). Since aging is characterized by high spatial heterogeneity, it is promising that combining ST techniques with other data sources (such as single-cell sequencing data) will provide an extensive and comprehensive understanding of the mechanisms that underlie aging.…”
Section: Imaging-based Techniquesmentioning
confidence: 99%